IMPLEMENTATION OF INTEGRATED DISEASE SURVEILANCE AND RESPONSE BY PUBLIC AND PRIVATE HEALTH FACILITIES IN TWO LOCAL GOVERNMENT AREAS OF OYO STATE (2012)
Integrated Disease Surveillance and Response (IDSR) was adopted in 1998 by the World Health OrganisationRegional committee for Africa as a strategy for strengthening the existing weak and multiple national surveillance system. Within the framework of IDSR strategy, all health facilities are required to have IDSR focal persons, ensure timely and regular provision of disease data to the Local Government Area (LGA) using approved IDSR reporting format and instruments. However, there is paucity of information regarding its implementation. This study was carried out to assess and compare the knowledge and practice of disease surveillance, and implementation of IDSR strategy at public and private health facilities in two LGAs of Oyo State, Nigeria. A comparative cross-sectional study was carried out in all health facilities in Ibadan North (urban) and Ibarapa East (rural) LGAs selected by cluster sampling technique. Surveillance focal person or a facility head designated personnel in each health facility was interviewed using a pretested semi-structured questionnaire. Information was obtained on knowledge of disease surveillance, pre-existing surveillance practices and IDSR implementation. Response to each variable was scored 1 for correct and 0 for incorrect response. Composite scores were computed given maximum scores of 29, 6 and 13 for knowledge, pre-existing surveillance practice and IDSR implementation scores respectively. Data were analysed using descriptive statistics and students t-test. One hundred and thirty-two health facilities [30 public (22.7%) and 102 private (77.3%)] were studied. There were 117(88.6%) fr om urban and 15(11.4%) from rural LGAs. Overall mean knowledge score was 16.1+ 4.1. Mean knowledge score in the public and private facilities were 15.2 + 3.4 and 16.4 + 4.2 respectively; and in the LGAs; 16.3+4.1 (Ibadan north) and 14.5+3.4 (Ibarapa East). Overall score for mean disease surveillance practice was 2.7+1.4. The mean disease surveillance practice score was 2.8+1.5 in public and 2.7+1.5 in private facilities. The overall median IDSR implementation score was 1.00 (min 0.00, max 11.00) .The median IDSR implementation score was significantly higher in public facilities 3.00 (min 0.00, max 11.00) compared with 1.00 (min 0.00, max 11.00) in the private facilities, p<0.05. No difference existed in the median implementation scores between Ibadan North, 1.00(min 0.00, max 11.00) and Ibarapa East,2.00(0.00-7.00) LGAs. Surveillance focal persons existed in only 11 facilities (8.3%). Mean scores for pre-existing surveillance practice where focal persons existed was 3.5+1.5 compared with 2.6+1.4 where none existed (p< 0.05). Median IDSR implementation scores in facilities with surveillance focal person was 3.00 (min 1.00, max 11.00) and 1.00 (min 0.00, max 11.00) where none existed (p<0.05). Knowledge and practice of disease surveillance as well as implementation of Integrated Disease Surveillance and Response strategy were generally below average in all the health facilities irrespective of status and location with poorer implementation in the private facilities. The existence of a surveillance focal person improved surveillance practice. There is a need to institute measures to improve awareness and participation of health facilities in disease surveillance to achieve set goals.